Reforming the society through knowledge and education : the role of Islamic reformism in Malaya, 1906-1941 - Wan Sulong, Wan Suhana (2009)
This paper attempts to look at the importance of knowledge and education among the reformists in Malaya, starting from the date of the publication of their first journal al-Imam in 1906 up to the Second World War. The discussion is mainly based on the articles published in the reformist journals and newspapers such as al-Imam, Neracha, al-Ikhwan and Saudara. The paper will show that throughout this period, knowledge and education are among the central themes which dominated Islamic reformist journals and newspapers. Within the published pages, readers could find views, debates and suggestions on this issue. Among others the paper will reveal the reformists‟ ideas and thoughts on the importance of seeking knowledge, locally or overseas; the importance of learning foreign languages; Malays‟ education in English and Malay schools; religious education; higher education for the Malays, etc. Basically, this study will reflect the reality of Malays‟ education under the British in Malaya and the problems faced by the Malays pertaining to their advancement in education. It will also reveal the status of Malays‟ education as compared to other races in Malaya during the respective period.